(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2019)
This essay discusses the production, funding, and circulation of Design Workshops (1940–44), a group of 16mm Kodachrome films produced at László Moholy-Nagy’s Chicago-based School of Design (formerly the New Bauhaus), to explore the role of colour theory and practice in the communicative agendas of Moholy and his corporate sponsor Walter Paepcke, chairman of the Container Corporation of America. As a symptomatic foray into the mid-century category of ‘communication’, the films collected as Design Workshops — at once documents of pedagogical theory and quasi-corporate promotional messages — involved moving images both in zones of pedagogical experimentation and in the more instrumental domains of public relations, packaging and brand management. In the case of Moholy-Nagy’s School of Design, colour experimentation and creative making in the synthetic materials of the post-war — Saran or plywood — were wedded to the inculcation of forms of democratic subjectivity (perceptual skills, epistemologies, creative capacities) that the artist saw as essential to post-war citizenship at mid-century. The essay demonstrates Moholy-Nagy and Paepcke’s overlapping investments in colour’s functional, communicative dimensions at the School, and argues that colour film production in Design Workshops fuelled a vanguard humanities vision at mid-century. The essay reads Design Workshops as an allegory of that vision and its limits, performing the work and pedagogical theory of the School for potential donors and funding agencies like the Rockefeller Foundation.